Scenarios for the integration of renewable gases into the German natural gas market – A simulation-based optimisation approach - Kolb, Sebastian; Plankenbühler, Thomas; Frank, Jonas; Dettelbacher, Johannes; Ludwig, Ralf; Karl, Jürgen; Dillig, Marius (Renewable & Sustainable Energy Reviews, 2021)
Natural gas plays an essential role in Germany's energy system, both in the heating and electricity sectors. In order to achieve climate goals, numerous technologies aim at substituting fossil with renewable gas. Those technologies start reaching technical maturity, yet they are mostly not economically competitive under the current market conditions. To find transition paths to resolve this issue this paper introduces the simulation-based optimisation model MIREG (Model for the Integration of Renewable Gases). Combining a system-dynamic simulation of the various renewable gas options with an optimisation model of the gas market, the model puts strong focus on the reproduction of gas market's mechanisms and the implications of a rising penetration of renewable gases. The model is then applied to analyse the effects of different developments of market conditions and funding strategies on the possible share of renewable gases in the German gas mix until 2050. Results show that if renewable gases are supposed to account for a significant share of gas consumed in Germany they either need to be funded substantially or market conditions have to change. For a share of 23% renewable gas in the gas mix CO2 prices for example would have to reach a level of 150 €/tCO2 by 2050 (300 €/tCO2 for 54%). The scenarios also indicate that in order to meet significant amounts of the German gas consumption with renewable gases, international solutions need to be aimed at e.g. by importing renewable gas from locations with high potential of renewable energy or by importing biomass.
CRIS-Team Scopus Importer:2021-01-29
Keywords: Biomethane; Energy system modeling; Power-to-Hydrogen; Power-to-Methane; Scenario analysis; Synthetic natural gas